Hogbomite from Fe-Ti oxide deposit, Boula-Nausahi igneous complex, keonjhar district, Orissa, India - Mohanty J. K. (Acta mineralogica-petrographica, 2000)
Primary and secondary hogbomites occurs both as well developed crystals and anhedral grains in Fe-Ti oxide ores of Boula-Nausahi igneous complex. Primary hogbomite is pyrogenic in nature haying formed from the magma at a low temperature. The secondary hogbomite has formed at the> expense^oftspinel by the substitution of Ti2+ for Mg and Fe3+ for Al3+ . EPMA of hogbomite showed 6-9.5<*.wt% tjiOi, 5T51 - 59 wt% A1203, 0-1.99 wt%, Cr203, 21.43-29.93 wt%, FeO(t), 0.02-0.23 wt%, MnO,'2.46-8.17 wt%, MgO and 1.03-1.84 wt% ZnO. The stoichiometric formula, Fe2+<2.7-5.09) Mg(o.8i-2.66) Ti<i. 1.156) Fe3+(o.432-i.i24) AI(m.86-i5.345) O32 suggests that hogbomite has an open structure as compared to associated magnetite and ilmenite.